ChemInform Abstract: An Efficient Route to Regioselective Functionalization of Benzo[b]thiophenes via Palladium‐Catalyzed Decarboxylative Heck Coupling Reactions: Insights from Experiment and Computation. Issue 20 (April 2016) - Yang, Daoshan; Liu, Yuxia; Sun, Pengfei; Zhang, Ning; Wei, Wei; Sun, Mingyang; Chen, Guang; Bi, Siwei; Wang, Hua
Abstract: The decarboxylative Heck coupling reaction of 3‐chlorobenzo[b]thiophene‐2‐carboxylic acids (I) with styrenes leads to desired (E)‐3‐chloro‐2‐styrylbenzo[b]thiophenes (III) in good to high yields, while the reactions with 1‐pentene and methyl acrylate fail.